Focusing quorum sensing signalling by nano‐magnetic assembly - Yongguang Guan; Chen‐Yu Tsao; David N. Quan; Ying Li; Lei Mei; Yingying Song; Boce Zhang; Yi Liu; Gregory F. Payne; William E. Bentley; Qin Wang (Environmental Microbiology, 2018)
Summary Quorum sensing (QS) exists widely among bacteria, enabling a transition to multicellular behaviour after bacterial populations reach a particular density. The coordination of multicellularity enables biotechnological application, dissolution of biofilms, coordination of virulence, and so forth. Here, a method to elicit and subsequently disperse multicellular behaviour among QS‐negative cells is developed using magnetic nanoparticle assembly. We fabricated magnetic nanoparticles (MNPs, ∼5 nm) that electrostatically collect wild‐type (WT) Escherichia coli BL21 cells and brings them into proximity of bioengineered E. coli [CT104 (W3110 lsrFG − luxS − pCT6 + pET‐DsRed)] reporter cells that exhibit a QS response after receiving autoinducer‐2 (AI‐2). By shortening the distance between WT and reporter cells (e.g., increasing local available AI‐2 concentrations), the QS response signalling was amplified four‐fold compared to that in native conditions without assembly. This study suggests potential applications in facilitating intercellular communication and modulating multicellular behaviours based on user‐specified designs.